The Inn at Ocean's Edge - Coble, Colleen (2015)
"A vacation to Sunset Cove was her way of celebrating and thanking her parents. After all, Claire Dellamore's childhood was like a fairytale. But with the help of Luke Elwell, Claire discovers that fairytale was really an elaborate lie...The minute she steps inside the grand Inn at Ocean's Edge, Claire Dellamare knows something terrible happened there. She feels it in her bones. Her ensuing panic attack causes a scene, upsetting her parents. Claire attempts to quiet her nerves with a walk on the beach, to no avail. She's at too great a distance to make out details, but she believes she witnesses a murder on a nearby cliff. When local police find no evidence of foul play, they quickly write off the "nervous" woman's testimony as less than credible. But Luke Elwell, home on leave from the Coast Guard, has reason to believe Claire. Years ago when his mother went missing, Luke's father suspected she'd been murdered. He died never having convinced the police to investigate. So when an employee of the grand hotel doesn't show up for work, Luke steps in to help Claire track down the missing woman. As Claire and Luke put together the pieces of a decades-old mystery, they discover that some family secrets refuse to stay buried. And some passions are worth killing for"--
Keywords: Family secrets -- Fiction; Murder -- Investigation -- Fiction; Man-woman relationships -- Fiction; Mystery fiction; Romantic suspense fiction